Ploidy Testing of Blastocoel Fluid for Screening May Be Technically Challenging and More Invasive Than That of Spent Cell Culture Media - Shi, Wenhao; Zhao, Zhenghao; Xue, Xia; Li, Qian; Yao, Yaxin; Wang, Dongyang; Wang, Jing; Lu, Sijia; Shi, Juanzi (Frontiers in Physiology, 2022)
Background Recent studies have demonstrated that both blastocoel fluid (BF) and spent cell culture media (SCM) have potential as materials for non-invasive or less-invasive pre-implantation genetic analysis. BF may allow more opportunity to obtain cell-free DNA from the inner cell mass (ICM), and it has a lower risk of containing contaminant DNA from cumulus cells, sperm and culture media. There are no data regarding the ICM as a gold standard to evaluate the chromosome constitution of BF or SCM for embryo liquid biopsy. Methods Two hundred eighteen donated human blastocysts were warmed and cultured in blastocyst culture media for 18–24 h. The corresponding SCM was collected, and only clear ICM was biopsied in blastocysts; otherwise, the whole blastocyst (WB) was biopsied. Quantitative PCR was performed to determine the DNA levels in the SCM and BF before and after amplification. ChromInst was used to amplify BF/SCM and blastocyst DNA before sequencing. Chromosomal copy number variation (CNV) was investigated to evaluate the chromosome constitution. Results In total, 212 blastocysts were available for SCM and BF collection. The technical success rates (next-generation sequencing data) were 100 and 69.8% (148/212) for SCM and BF, respectively. Among the 148 blastocysts with both SCM and BF data, 101 were euploid and 47 were aneuploid based on ICM (n = 89) or WB (n = 59) analysis as the gold standard. Among all blastocysts, SCM was comparable to BF [specificity: 80.2 versus 61.4% (P = 0.005, χ2 test); sensitivity: 91.5 versus 87.2% (P = 0.738, χ2 test); negative predictive value (NPV): 95.3 versus 91.2% (P = 0.487, χ2 test); positive predictive value (PPV): 68.3% versus 51.3% (P = 0.042, χ2 test)]. The SCM and BF samples were 83.8% (124/148) and 69.6% (103/148) concordant with the corresponding ICM/WB samples when only two categories, euploid or aneuploid/mosaic, were grouped to calculate the concordance. Conclusions Compared with BF, SCM has superior diagnostic performance, and it is non-invasive for embryos. Clinical Trial Registration [http://www.chictr.org.cn], identifier [ChiCTR-BPD-17014087].